A study of genus Zingiber: the role of condiments in science - Anggra Paramita; Indra Wibowo; Muhammad Insanu (Institut Teknologi Bandung, 2021)
Zingiberaceae family has been widely used as an herbal medicine from generation to generation. The literature review of Zingiber genus, which is part of Zingiberaceae, was conducted to provide information and to determine the correlation between bioactive compounds and pharmacological properties with their empirical uses. Articles about genus Zingiber were collected from online databases (e.g., Directory of Open Access Journal, PubMed, ResearchGate, ScienceDirect, and Springer), they were sorted based on inclusions criteria such as related to bioactive compounds and biological activities of the samples and also articles for the last ten years. Merely articles with DOI were reviewed. The screening process resulted in 52 reports being reviewed and grouped based on each plant's bioactive contents and pharmacological properties. The major constituents in genus Zingiber are essential oils. Therefore, the dominant activities found in this genus was related to antimicrobial and antioxidant. Furthermore, the other activities of plants were related to the bioactive compounds and their current uses. The empirical uses of these rhizomes were in line with the bioactive compounds and biological activities.